2019
DOI: 10.3389/fcimb.2019.00340
|View full text |Cite
|
Sign up to set email alerts
|

IFNL4 Genotypes Predict Clearance of RNA Viruses in Rwandan Children With Upper Respiratory Tract Infections

Abstract: Polymorphisms in the interferon lambda gene locus (IFNL) such as the IFNL4 genetic variants rs12979860 and rs368234815 are predictive of resolution of hepatitis C virus infection, but information about the impact of these variants in other infections is scarce. This study aimed at determining the potential impact of IFNL4 variation for the clearance of respiratory tract pathogens in Rwandan children (≤5 years old, n = 480) seeking medical care for acute respiratory infections. Nasopharyngeal swabs were retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 25 publications
7
46
2
Order By: Relevance
“…Recently, a genetic association was reported for IFNL4 -rs12979860-T and rs368234815-dG alleles with impaired clearance of respiratory RNA viruses in nasal swabs of children from Rwanda (11). The observed effect was in the same direction as for clearance of HCV reported in many studies, suggesting that the negative impact of IFN-λ4 on clearance of RNA viruses is not limited by HCV but extends to respiratory RNA viruses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a genetic association was reported for IFNL4 -rs12979860-T and rs368234815-dG alleles with impaired clearance of respiratory RNA viruses in nasal swabs of children from Rwanda (11). The observed effect was in the same direction as for clearance of HCV reported in many studies, suggesting that the negative impact of IFN-λ4 on clearance of RNA viruses is not limited by HCV but extends to respiratory RNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because respiratory symptoms recorded during clinic visits in our study were very common (were experienced by 97.7% of children during follow-up), and occurred very early in life, with the median timing of the first RI episode being 16 weeks of age. Furthermore, RI episodes were defined very broadly, without stratifying by specific viral etiology, as was done in the study in Rwanda (11). In addition to bacterial and viral etiology, respiratory symptoms might also be caused by helminths (pinworms, roundworms, etc) transiting through the lungs during their life cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used, for the rst time to our knowledge in the eld of SARS-CoV-2, nucleic acid extracts generated from swabs during the diagnostic processing COVID-19 to evaluate the host's genetic pro le. This approach, originally devised for other respiratory viruses, had suggested that the IFN lambda system could be a determinant of the outcome of such infections [11]. Albeit we could not nd any signi cant relation between the IFN lambda system and the outcome of COVID-19, the perspective of using genetic material obtained from swabs could be of major relevance for wide, population-based studies of the genetic background of people infected by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 79%
“…As proof of the key role type III IFNs in the regulation of immunity response, single nucleotide polymorphisms in genes IFNLs were strongly associated with outcomes to viral infection [14]. It has been reported that the homozygosity for IFNL3 (rs12979860) and IFNL4 (rs368234815) variants, overrepresented in African descent, is associated with a reduction of viral clearance in children affected by acute respiratory infections sustained by Rhinovirus and Coronavirus [11]. Since subjects with rs12979860 CC and rs368234815 TThaplotype were reported to be more effective in clearing RNA viruses, possibly due to an up-regulation of in ammatory pathways, we aimed to assess whether the outcome of SARS-CoV-2 infection is conditioned by these polymorphisms.…”
Section: Discussionmentioning
confidence: 99%